Reference service: Bagaimana implementasinya Di UPT Perpustakaan Universitas Negeri Malang? - Achmad Qorni Novianto; Nining Nugrahini (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2023)
Technological developments and changes in the characteristics of users make reference services in libraries experience a series of developments. Librarians are not only required to master the various reference collections available in the library but also must understand various types of other information sources that contain credible information. By utilizing existing technology, virtual reference services can improve the accessibility of users so that they do not need to come to the library physically. The types of reference services implemented at UPT UM Libraries include (1) guidance on using reference collections. (2) direct information retrieval guidance, and (3) virtual reference services.